Synthesis of poly(o-phenylenediamine) micro/nanostructures and application in fast humidity sensing. (15th June 2022) - Zhou, Tieli; Ma, Jingxi; He, Jianxin; Liu, Zhenxiang; Yang, Liu; Hou, Jumin; Sun, Maocheng; Wu, Shuqing; Ruan, Weidong
Graphical abstract: Highlights: Fast humidity sensors based on PoPD films were fabricated. The H3 PO4 doped PoPD films show the highest response, the fastest response/recovery behavior, excellent repeatability and good stability. The H3 PO4 doped PoPD films demonstrate great potential applications on humidity detections. Abstract: Micro/nanostructured poly(o-phenylenediamine) (PoPD) thin films were synthesized by a templateless method in the presence of inorganic/organic acids as dopants, including hydrochloric acid (HCl), phosphate acid (H3 PO4 ), camphorsulfonic acid (C4 H6 O6 ), and sulfuric acid (H2 SO4 ). It was found that the morphology of products was dependent on the dopant species seriously at the same experimental conditions. The fibrous, big and long microbelts, narrow and short microbelts, wide and short microbelts, and nanorods were obtained correspondingly. The as-synthesized one-dimensional micro/nano-belt/rod structures of PoPD were firstly used for the fabrication of resistor-type humidity sensors. All the samples showed humidity sensing ability. However, the performance of the sensitivity was obviously different with changing the doping acids. Compared with other acids, PoPD doped with phosphate acid has the highest sensitivity, the quickest adsorption–desorption time, and the longest lifetime in a wide range of humidity. Between the two relative humidity (RH) of 11% and 97%, the response and recovery time on phosphate acid doped PoPD were 5 and 21 s, respectively. Both the response time and the recovery time are very fast and show great potential in practical applications.